ILLUSTRATED SYNOPSIS OF THE FISHES OF THE FAMILY SCIAENIDAE OF INDIA - Lalmohan, R S (Indian Journal of Fisheries, 2011)
The paper gives brief descriptions of 36 species of sciaenids found in Indian waters, along with a key for identification. Thirty species are illustrated